Recent developments in the surgical management of paediatric epilepsy. Issue 8 (17th January 2017) - Ravindra, Vijay M; Sweney, Matthew T; Bollo, Robert J
Abstract : Among the 1% of children affected by epilepsy, failure of pharmacological therapy and early age of seizure onset can lead to worse long-term cognitive outcomes, mental health disorders and impaired functional status. Surgical management often improves functional and cognitive outcomes in children with medically refractory epilepsy, especially when seizure remission is achieved. However, surgery remains underused in children with drug-resistant epilepsy, creating a large treatment gap. Several recent innovations have led to considerable improvement in surgical technique, including the recent development of minimally invasive diagnostic and therapeutic techniques such as stereotactic EEG, transcranial magnetic stimulation, MRI-guided laser ablation, as well as novel paradigms of neurostimulation. This article discusses the current landscape of surgical innovation in the management of paediatric epilepsy, leading to a paradigm shift towards minimally invasive therapy and closing the treatment gap in children suffering from drug-resistant seizures.